2022
DOI: 10.1016/j.jiac.2021.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood favipiravir levels are inversely associated with ferritin levels and induce the elevation of uric acid levels in COVID-19 treatment: A retrospective single-center study

Abstract: Introduction Measurement of blood Favipiravir (FPV) levels and accumulation of data in COVID-19 patients are critical for assessing FPV efficacy and safety. We performed a retrospective study based on measurements of blood levels of FPV and related factors in COVID-19 patients admitted to our hospital. Furthermore, we also investigated the association between blood FPV levels and uric acid level alterations before and after FPV administration. Methods We enrolled 27 COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In addition, due to the risk of teratogenicity and embryotoxicity associated with this chemical [40], the treatment of pregnant women and children requires more caution. It has also been suggested that blood favipiravir levels may be negatively correlated with blood ferritin levels in the treatment of patients with moderate to severe COVID-19 [41], and a clinical study has shown that favipiravir is ineffective in patients with elevated ferritin and that patients with high blood favipiravir levels frequently have elevated uric acid levels [42], implying that monitoring blood favipiravir levels is especially important when treating patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to the risk of teratogenicity and embryotoxicity associated with this chemical [40], the treatment of pregnant women and children requires more caution. It has also been suggested that blood favipiravir levels may be negatively correlated with blood ferritin levels in the treatment of patients with moderate to severe COVID-19 [41], and a clinical study has shown that favipiravir is ineffective in patients with elevated ferritin and that patients with high blood favipiravir levels frequently have elevated uric acid levels [42], implying that monitoring blood favipiravir levels is especially important when treating patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that the platform could be applied for the quantification of the serum levels of 15 different drugs (carbamazepine [CBZ], phenytoin [PHT], lamotrigine [LTG], disopyramide, flecainide, lidocaine, mexiletine, procainamide, propafenone, quinidine, sotalol, voriconazole [VRCZ], mycophenolic acid, imatinib, and pazopanib) with almost the same procedures and exactly the same HPLC-UV apparatus. Furthermore, the method was also applied to the clinical evaluation of the blood levels of favipiravir [ 12 , 13 ] and VRCZ [ 14 ] at different hospitals in Japan. However, with a few exceptions such as favipiravir and VRCZ, the method using the above platform is just beginning to be applied to the clinical evaluation of blood levels of other kinds of drugs during therapy in clinical practice.…”
Section: Introductionmentioning
confidence: 99%